Peningkatan Pengetahuan Ibu tentang Pengelolaan Makanan Pendamping ASI (MP-ASI) - Dewi Ayu Ningsih; Nirma Lidia Sari (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Effort of the optimalization the growth and development of children required adequate nutritional intake. Breast milk and complementary feeding were the main sources in supporting child growth. The timing to starting complementary feeding greated affects the quality of a child's health. The practice of giving complementary feeding early can increased the risk of high incidence of infections and growth disorders. Children who did not got optimal complementary feeding, 6.5 times more likely to experience growth disorders. Lack of understanding in the management of infant and child food, low education, socioeconomic factors were factors that cause malnutrition and infection problems in children under five, especially under the age of 24 months. The purpose of this community service was increased the knowledge of breastfeeding mothers and mothers who have children under the age of 2 (two) years about the Management of Complementary Feeding. The form of community service activitie was socialization method. The socialization method through face-to-face used presentation media and leaflets. The pretest was carried out before the extension activities with the result that the mother's level of knowledge about the management of complimentary feeding before the delivery of the extension material was in the Poor category with the average value of the evaluation results reaching 50.8%. The results of the posttest after being given the extension material showed an increase in the mother's knowledge about the management of complementary feeding with an average evaluation value of 85%, which was in the good category. There was an increase of 34.2% towards the increase in mother's knowledge about the management of complementary feeding. The result of this community service that providing information about the management of complementary feeding was very necessary so that breastfeeding mothers having good knowledge about the management of complementary feeding and can contribute to changes in mother's behavior in dealing with the stages of giving complementary feedingto their children. Then, giving the right complementary feeding can had been an impact on health optimal child development.